Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.46867/ijcp.2017.30.01.01
|View full text |Cite|
|
Sign up to set email alerts
|

How and Why Does Category Learning Cause Categorical Perception?

Abstract: Learning to categorize requires distinguishing category members from non-members by detecting the features that covary with membership. Human subjects were trained to sort visual textures into two categories by trial and error with corrective feedback. Difficulty levels were increased by decreasing the proportion of covariant features. Pairwise similarity judgments were tested before and after category learning. Three effects were observed: (1) The lower the proportion of covariant features, the more trials i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…The work [ 23 ] proposes a computational model of categorical perception with which the authors investigate different learning processes. They adopt a functional approach based on machine learning, including an auto-encoder (AE; [ 26 ]) and a classifier.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The work [ 23 ] proposes a computational model of categorical perception with which the authors investigate different learning processes. They adopt a functional approach based on machine learning, including an auto-encoder (AE; [ 26 ]) and a classifier.…”
Section: Discussionmentioning
confidence: 99%
“…These models take different approaches, as they focus on the interaction between low-level and high-level information at different neuronal sites (e.g. apical and basal dendrites; [ 19 ]), systems supporting speech production [ 20 ], self-organising mechanisms [ 21 ], visual competitive hierarchies [ 22 ], and effects of supervised signals [ 23 ]. Other models of CP investigate Bayesian inferential mechanisms [ 24 ] and embodied evolutionary influences [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…de Leeuw et al (2016) reported a similar effect of task difficultly on acquired equivalence and distinctiveness effects using more complex stimuli. Conversely, Pérez-Gay et al (2017) did not find an effect of stimulus discriminability on categorical perception effects, but their stimuli were textures generated by tessellation of simple checkerboard patterns, and it is arguable that even their most discriminable stimuli were substantially more similar than any of the stimuli used by Hall et al (2003) or by Meeter et al (2009). One explanation for this effect of discriminability might be found in the suggestion made by Sutherland and Mackintosh (1971) that attention to very salient stimuli might change more slowly than to less salient stimuli, a principle that has been incorporated into other models of associative learning (e.g., Suret & McLaren, 2003, 2005).…”
Section: Discussionmentioning
confidence: 98%
“…One such factor is that Bad News only presents examples of one category (i.e., fake news) rather than two categories (i.e., true and fake news). Most research that has successfully improved discernment between two categories has done so by presenting examples of both categories (Higgins & Ross, 2011;Pérez-Gay et al, 2017). This allows for within-and between-category comparisons, which have both been found to be indispensable for category learning (Hammer et al, 2008).…”
Section: The Design Of Bad Newsmentioning
confidence: 99%